2012
DOI: 10.1016/j.lwt.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the emulsifier sodium stearoyl lactylate and of the enzyme maltogenic amylase on the quality of pan bread during storage

Abstract: a b s t r a c tEmulsifiers and enzymes are used as anti-staling agents in bakery products, providing increased shelf life, which is especially interesting for industrialized breads, such as pan bread. The objective of this study was to evaluate the effects of the emulsifier sodium stearoyl lactylate (SSL) and of the enzyme maltogenic amylase (MALTO) on the quality of pan bread during storage. A 2 2 complete factorial experimental design was followed and the Response Surface Methodology (RSM) was used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 10 publications
3
41
0
1
Order By: Relevance
“…The first scientific observation that led to the discovery of immobilized enzymes was made in 1916 [1]. It was demonstrated that invertase exhibited the same activity when absorbed on a solid, such as charcoal or aluminum hydroxide, at the bottom of the reaction vessel as when uniformly distributed throughout the solution.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The first scientific observation that led to the discovery of immobilized enzymes was made in 1916 [1]. It was demonstrated that invertase exhibited the same activity when absorbed on a solid, such as charcoal or aluminum hydroxide, at the bottom of the reaction vessel as when uniformly distributed throughout the solution.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Applications of enzymes in food industries include baking [1], dairy products [2,3], starch conversion [4] and beverage processing (beer, wine, fruit and vegetable juices). In textiles industries, enzymes have found a special place due to their effect on end products [5].…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol monostearate (GMS) is a colourless, odourless, and sweet-tasting flaky powder that is hygroscopic, so it is widely used as an emulsifier in the food industry (Galloway et al 1989;Carrillo-Navas et al 2014). Calcium stearoyl lactylate (CSL) is used to enhance dough conditioners/strengtheners and softeners in starch products (Gomes-Ruffi et al 2012). The diacetyl tartaric acid ester of monoglycerides (DATEM) has been shown to modify the resistance and extensibility of dough by different proposed mechanisms (Ponzio et al 2013).…”
Section: Food Technology and Economy Engineering And Physical Propermentioning
confidence: 99%
“…Crumb firming is unavoidable, however it can be slowed down by adding bread emulsifiers, enzymes or hydrocolloids in the bread recipe. Complex interaction between bread emulsifiers and enzymes with the flour components improves bread quality and assists in retarding crumb firming (Gomes-Ruffi et al, 2012;Purhagen et al, 2011). He and Hoseney (1990) and Faridi and Rubenthaler (1984) had all demonstrated that bread with high moisture content in crumb had lower firmness value during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Crumb firming is the condition which the crumb becomes dry and crumbly resulting in gradual reduction of bread eating properties, or more commonly described as bread staling. The common causes for bread staling are starch retrogradation, proteins and protein-starch interactions and moisture migration (Gomes-Ruffi et al, 2012; Gray and Bemille, 2003). Crumb firming is unavoidable, however it can be slowed down by adding bread emulsifiers, enzymes or hydrocolloids in the bread recipe.…”
mentioning
confidence: 99%